Pengaruh Penggantian Rumput dengan Pelepah Sawit Ditinjau dari Segi Kecernaan dan Fermentabilitas Secara In Vitro Gas - Suryadi, Suryadi; Afdal, Muhammad; Latief, Abdul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The objective of the research was to study the influence of grass to oil palm frond substitution on the digestibility and fermentability  in vitro gas tehniques.  The research  used arranged in a randomized complete design with 5 treatments and 4 replication.  The treatments that was substitution of the grass to oil palm frond at level : 0, 25, 50, 75 and 100% in  ration. The result of the sudy showed that substitution of the grass to oil palm frond  was significantly different (P < 0.05) on the digestibility of dry matter but not significantly different (P > 0.05) on the digestibility of organic matter, acid degreeand gas production.  It could be concluded that the used of grass to oil palm frond substitution at the level   25% had better the digestibility  and fermentability compared to other treatments.